Plant species richness, green spaces, and preterm birth risk in urban areas - Mengyi Li; Qiping Fan; Yi Sun; Tarik Benmarhnia; Jiu-Chiuan Chen; Anqi Jiao; John Molitor; David A. Sacks; Jeff M. Slezak; Vicki Y. Chiu; Chantal C. Avila; Darios Getahun; et al. (Environment International, 2025)
Background: Growing evidence suggests that urban biodiversity may influence human health, though this relationship remains incompletely understood. While green spaces have shown beneficial effects on birth outcomes, the specific role of plant species richness has not been investigated in relation to preterm birth (PTB, <37 weeks’ gestation). Methods: Using Kaiser Permanente Southern California electronic health records (2015–2021), we analyzed 232,452 births to examine associations between plant species richness and PTB. Plant species richness was assessed at the maternal neighborhood level, defined using circular buffers of 1.5 km around maternal residences. Results: We found that increased plant species richness was associated with decreased PTB risk (adjusted odds ratio per interquartile range: 0.959, 95 % CI: 0.941, 0.977). The observed association persisted after further adjustment for multiple green space indicators. The proportions of mediation effects attributable to mean temperature during pregnancy ranged from 7.0 % to 7.8 % across plant species diversity indicators. In the subgroup analysis, plant species diversity demonstrated significantly stronger protective associations against PTB among mothers exposed to higher levels of Ozone, high ambient temperatures, and those gave birth during the pandemic period. Conversely, protective associations were more pronounced among mothers with lower NO2 exposure during pregnancy. Notably, the significant relationship between plant species richness and reduced PTB persisted in pandemic-period analyses after adjusting for COVID-19 infection during pregnancy. Conclusions: Our findings highlight a complex interplay of sociodemographic and environmental factors influencing PTB risks and underscore the critical need for public health interventions that consider the unique attributes of urban green space.